Manejo ortodóncico de caninos maxilares retenidos - Gómez-Gómez, Sandra Liliana; Jaramillo-Vallejo, Pedro María (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The orthodontic management o/ can ine retention is based in an adecuate diagnosis, treatment and biomechanics. There is an ideal orthodontic biomechanics when there is control in the action and reaction zone. Various techniques are used: edgewise, segmentary technique, box loops, bal/ista spring and magnets. Most importantly, an accurate diagnosis leads to a priority list that guides to an adecuate interdisciplinary management.